Education Institutions Based On Indonesian Legal Country Perspective - Redyanto Sidi (EDUTECH, 2020)
The concept of the rule of law (rechtstaats) in Indonesia must be in accordance with the values reflected in Pancasila. A complete understanding of the concept of the rule of law based on Pancasila can be seen from the process and background of the birth of the formulation of the Opening of the 1945 Constitution which is a statement of the will of the birth of the Indonesian state, as well as a philosophical basis and state goal. The elements of the Indonesian rule of law constitute values derived from the whole process of the birth of the state of Indonesia, the basis of the philosophy and ideals of the Indonesian state law. Therefore, the opening position of the 1945 Constitution which also contains the formulation of the Pancasila, became the highest source of law for the Indonesian law state. The Preamble to the 1945 Constitution is the highest abstraction value and the value contained in the preamble is the guiding method for the preparation of the articles in the 1945 Constitution so as not to deviate from the values that form the basis of the country's philosophy and ideals